PERSEPSI MASYARAKAT LOKAL TERHADAP USAHA TANI KARET (Hevea brasiliensis) DI DESA LAJA KECAMATAN TANAH PINOH BARAT KABUPATEN MELAWI - Kharismanto, Dedang; Zainal, Sofyan; Oramahi, H A (JURNAL HUTAN LESTARI, 2019)
Rubber farming has been in demand by the people of Laja Village since 1990's as a livelihood by utilizing shifting fields within the forest. Some people's income from the results of rubber farming is very large, especially during the dry season, where people tap into rubber sap every day. Rubber prices experienced a decline that was felt by rubber farmers and in the rainy season the people could not tap rubber sap, the people were forced to find alternative jobs, such as gold mining and other jobs. This situation certainly raises different perceptions of society. This study aims to determine the public perception of rubber farming and analyze the relationship between knowledge, income and cosmopolitan factors. This study uses descriptive and associative surveys with interview techniques and the questionnaire contains a number of questions posed to respondents, collecting data using random purposive sampling. Data analysis using descriptive analysis of the chi square test and inferential analysis using the non-parametric statistical test of the Kendall Tau correlation. The number of respondents in the study were 72 people. The results of this study indicate that public perceptions tend to be positive, moderate level of knowledge, low income level, high cosmopolitan level. There is a positive and significant relationship between the level of knowledge and perception, and there is no significant and no relationship between income levels and cosmopolitan with community perceptions.Keywords: Local community Perception, Rubber Farmers